La columna lingüística de Juan B. Selva en "La Obra" (1923-1927) - Lidgett, Esteban (2023)
This paper addresses the linguistics column that Juan B. Selva published in the pedagogical journal La Obra between 1923 and 1927, with the aim of examining both the criteria of authority regarding linguistic knowledge, as well as the ideological assessments and attitudes expressed by the author in relation to the linguistic phenomena he describes. The analysis of the column (which was published in a context in which Argentina was witnessing the institutionalization of linguistics and the expansion of debates on language in the press) allows us to corroborate the centrality of normative issues, a characteristic feature of the genre. However, it also reveals the emergence of a discourse that rejects prescriptive positions and, instead, seeks scientific explanations for the linguistic phenomena it records.